(untitled) (Progressive Agriculture, 2017)
Gher farming with shrimp and prawn (seafood) is blooming in the south-west region of Bangladesh, impacting positively on household level nutritional security, employment generation and foreign currency earning. Such positive impacts increased the importance of seafood production and trade to the international market from Bangladesh. Out of several food safety requirement of international market, seafood traceability is a key issue for Bangladeshi producers. To develop a traceability system about 200,000 gher farmers were registered by DoF with the support of UNIDO project and a paper based traceability system was developed since 2009. This study was designed to understand existing traceability system, trend of gher ownership changes and its impact on the traceability in term of its strength and weakness. Three gher farming clusters in three upazilas of Bagerhat district were selected to carry out this study to assess the facts above using focus group discussion, key informant interview, questionnaire survey, physical observation, and literature review. The micro-level observation on the gher and its ownership changes were critically analyzed taking the Google Earth images from the farming cluster in the selected upazilas. The study revealed that gher farming has huge positive impacts on total farm productivity, income, and farmers well-being however, land ownership changes impacting negatively on existing traceability of farms. It was found that out of 167 ghers in three clusters, a massive change of gher ownership happened over the last 10 years. Under this situation existing traceability system cannot sustain for a long time. Therefore, land administration system should be brought under digital system and e-traceability needs to be implemented by the collaborative initiative of the Department of Fisheries and the Ministry of Land. Progressive Agriculture 28 (2): 156-166, 2017